2006
DOI: 10.1200/jco.2005.04.0436
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial Comparing Nitroglycerin Plus Vinorelbine and Cisplatin With Vinorelbine and Cisplatin Alone in Previously Untreated Stage IIIB/IV Non–Small-Cell Lung Cancer

Abstract: Use of nitroglycerin combined with vinorelbine and cisplatin may improve overall response and TTP in patients with stage IIIB/IV NSCLC. The arm A regimen is being evaluated in a large phase III trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(101 citation statements)
references
References 51 publications
5
94
0
2
Order By: Relevance
“…However, even third-generation regimens such as docetaxel and platinum result in response rates of 24% to 36% in the intention-to-treat population, and in 8 to 14 months in median overall survival among patients with advanced nonsmall cell lung cancer (NSCLC) with good performance status (27 -29). We showed that a combinational use of nitroglycerin plus vinorelbine and cisplatin regimen improves the response rate to 72% and median time to progression (TTP) to 11 months in comparison with vinorelbine and cisplatin alone in previously untreated stage IIIB/IV patients with NSCLC in a phase II trial, showing the additional effect of nitroglycerin on vinorelbine and cisplatin regimen (30). Taxanes, including docetaxel and paclitaxel, are widely used for chemotherapy in patients with advanced NSCLC (29).…”
mentioning
confidence: 99%
“…However, even third-generation regimens such as docetaxel and platinum result in response rates of 24% to 36% in the intention-to-treat population, and in 8 to 14 months in median overall survival among patients with advanced nonsmall cell lung cancer (NSCLC) with good performance status (27 -29). We showed that a combinational use of nitroglycerin plus vinorelbine and cisplatin regimen improves the response rate to 72% and median time to progression (TTP) to 11 months in comparison with vinorelbine and cisplatin alone in previously untreated stage IIIB/IV patients with NSCLC in a phase II trial, showing the additional effect of nitroglycerin on vinorelbine and cisplatin regimen (30). Taxanes, including docetaxel and paclitaxel, are widely used for chemotherapy in patients with advanced NSCLC (29).…”
mentioning
confidence: 99%
“…In addition, it has been reported that NO donor drugs are HIF-1α inhibitors and attenuate hypoxia-induced chemoresistance to taxanes and vinorelbine (34). In a randomized phase 2 trial, a combination of GTN plus vinorelbine and cisplatin was shown to improve the response rate and time to progression in comparison with vinorelbine and cisplatin alone in previously untreated patients with stage IIIB/IV NSCLC (38). Furthermore, the NO-cGMP signaling pathway has been reported to have a strong association with NO-induced attenuation of chemoresistance under hypoxic conditions (30).…”
Section: Discussionmentioning
confidence: 99%
“…Topical application of nitroglycerin ointment to the skin of mice with breast cancer resulted in an increased blood flow only in the neoplastic tissue, thereby increasing macromolecular drug delivery to the tumor. Clinical evaluations of nitroglycerin used in combination with conventional low-molecular weight anticancer agents were recently undertaken by Yasuda et al (35,36) and Siemens et al (37); both studies reported significant clinical improvement in therapeutic response, indicating that NO clearly benefits patients undergoing chemotherapy (11).…”
Section: Factors Affecting Enhanced Permeability and Retentionmentioning
confidence: 99%